XML-basierte Anreicherung von Texten - Potentiale für Verlage - Felix Haußer (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Buchwissenschaft, Professur für Buchwissenschaft, insb. E-Publishing und Digitale Märkte, 2014)
– The German book market has been changing during the last decade. Electronic publishing has started to play a significant role and continues to become more and more important. New technological advancements lead to new challenges for pub-lishers as well as sellers. The paper XML-based Text Enrichment. Potentials for Publishers discusses how the usage of XML-technologies can help to manage these challenges. The paper focuses on a presentation of applied XML-technologies which are required for semantic text enrichment and cross-platform publishing (XML, XSD, DTD, XSLT, XPATH, XSL-FO, CSS and EPUB). For illustration purposes, XML-technologies are presented using a semantically enriched version of Kafka's Die Verwandlung, created by the author of this paper. Furthermore, these technol-ogies will be used to build a content-management-system (CMS), which allows the integration of new text files into a methodical workflow. The paper shows and emphasizes the potential of XML-based text enrichment and content management, especially for publishers who use or plan to use digital sales channels. In order to minimize the risks that come with the implementation of CMS, innovation and change management must prepare for and accompany these processes.
urn:nbn:de:bvb:29-opus4-48842
Keywords: 650; Content Management; Cross Platform Publishing; Markup Language; Publishing Industry; Text Enrichment; XML-Technologies; Verlagswesen; Content Management; Elektronischer Datenaustausch